Gender Differences in Clinical Characteristics of Korean Temporomandibular Disorder Patients - Jung-Hwan Jo; Jin-Woo Chung (Applied Sciences, 2021)
The aims of this study were to investigate the gender differences in signs and symptoms of Korean Temporomandibular Disorder (TMD) patients based on Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) and psychosocial characteristics. A total of 1052 patients with TMD were evaluated with a questionnaire for medical history, clinical symptoms, and contributing factors, clinical examination based on RDC/TMD, and radiographic examination. RDC/TMD axis II and Symptom Checklist-90-Revision (SCL-90-R) were administered to evaluate pain-related disability level and psychological status of patients. The prevalence of TMD was higher in women than men, and the women were older than the men. The women showed higher prevalence of myogenous pain, mixed pain, disc displacement without reduction, osteoarthritis, headache, subjective insomnia, pain intensity, number of positive muscle palpation, and the high disability group in the grade chronic pain scale. Gender was associated with the number of positive muscle palpation and maximum mouth opening. Pain intensity was not associated with gender, but with number of systemic comorbidities. Subjective symptoms, and clinical and psychological characteristics of patients with TMD showed gender differences. To achieve understanding of patient and increase of success rate of treatment of TMD, gender should be considered in patient evaluations and treatment approaches.